Statistical modeling of river water quality index - Mohd Ali, Zalina (2019)
Water quality index (WQI) is a unitless number that indicates overall water quality at a specific time and location using several important water quality variables. In Malaysia, general WQI which is based on water quality expert opinion has been introduced by the Department of Environment (DOE) to describe the status of a specific location at identified rivers. The accuracy of DOE-WQI measured by the experts is assessed using four important phases namely variables selection, weights determination, variables transformation and variables aggregation, i.e. WQI calculation. However, the experts opinion approach is found to be the most subjective in nature.